2019
DOI: 10.1029/2019gl084309
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐Forced Symmetric Instability at a Transient Mid‐Ocean Front

Abstract: Mooring and glider observations and a high‐resolution satellite sea surface temperature image reveal features of a transient submesoscale front in a typical mid‐ocean region of the Northeast Atlantic. Analysis of the observations suggests that the front is forced by downfront winds and undergoes symmetric instability, resulting in elevated upper‐ocean kinetic energy, restratification, and turbulent dissipation. The instability is triggered as downfront winds act on weak upper‐ocean vertical stratification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
3
37
1
Order By: Relevance
“…We observe neither of these features in W025 or in the other simulations. A recent study (Yu, Garabato, Martin, Evans, et al, 2019) presents observational evidence for SI in O(100 m) mixed layers, wherein the authors report a well-defined SI layer beneath a convective layer, similar to earlier large-eddy simulation studies (Taylor & Ferrari, 2010). For the reasons described above, we do not see such an SI layer in our simulations.…”
Section: Profiles Of the Vertical Buoyancy Flux B Wsupporting
confidence: 87%
“…We observe neither of these features in W025 or in the other simulations. A recent study (Yu, Garabato, Martin, Evans, et al, 2019) presents observational evidence for SI in O(100 m) mixed layers, wherein the authors report a well-defined SI layer beneath a convective layer, similar to earlier large-eddy simulation studies (Taylor & Ferrari, 2010). For the reasons described above, we do not see such an SI layer in our simulations.…”
Section: Profiles Of the Vertical Buoyancy Flux B Wsupporting
confidence: 87%
“…Given that the scale of the fastest-growing MLI is close to the local deformation radius in the SML (i.e., L ; NH/f, N is the buoyancy frequency in the SML, H is the SML thickness, f is the local Coriolis parameter), MLI spatial scales vary from 1 to 10 km, requiring a model horizontal grid spacing of 0.55 km to capture 90% of regions globally in all seasons (Dong et al 2020b). Hence, submesoscale eddies generated by MLI can be mostly resolved by current-capability nested models, permitted in a few leading-edge global models (e.g., Capet et al 2008;Mensa et al 2013;Rocha et al 2016a,b;Sasaki et al 2017;Su et al 2018;Dong and Zhong 2018;Dong et al 2020a), and studied in specialized observations (e.g., Callies et al 2015;Buckingham et al 2016;Sarkar et al 2016;Viglione et al 2018;Little et al 2018;Yu et al 2019a;Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(3) implies that SI is associated with stronger (i.e., larger horizontal buoyancy gradient) fronts than MLI. Many studies have shown the SML possesses SI in the presence of strong horizontal buoyancy gradients (D'Asaro et al 2011;Thomas et al 2013;Haney et al 2015;Ramachandran et al 2018;Savelyev et al 2018;Viglione et al 2018;Buckingham et al 2019;Du Plessis et al 2019;Yu et al 2019b). SI are also potentially present in the bottom boundary layer (Wenegrat and Thomas 2020;Yankovsky et al 2020) as are MLI (Wenegrat et al 2018a;Dong et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The studied mesoscale process here is more like a coherent vortex in Tarshish et al (2018). It should also be noticed that the sub-mesoscale symmetric instability possibly exists universally and characterizes a large proportion of the ocean (Yu et al, 2019b), which also plays an important role in modulating the upper oceans stratification (Yu et al, 2019a,b), for example, the sub-mesoscale processes could be five times larger than the mesoscale processes in modulating the vertical heat transport (Su et al, 2018). However, due to the limited resolution of the used simulation, the sub-mesoscale processes cannot be well resolved.…”
Section: Resultsmentioning
confidence: 84%